Escuta, e a Terra te entrega o tempo presente: variações de uma clínica performática - Andrade, Sabrina Batista (2024)
This thesis addresses common dimensions between clinics, arts and politics. Through the transversality between these fields, signs are sought that favor an extemporaneous listening by the means of the clinical act through its performative force. Such signs follow the path of the becomings and the events inside and outside the clinical office. Throughout a listening that considers the existence of the outside dimension of the language, this practice utilizes elements from the psychoanalytical ritualistic but not necessarily its symbolic content, supposedly subjectivized. The purpose of this experimentation, composed of unique ethical and aesthetic issues, is to free bodies and their expressions of the recurrent captures produced by the neoliberal ethos and its new marketing guises. The aim is to achieve the production of health that is insubordinate to the status quo, favoring other vital trajectories, along with a clinical exercise attentive to deviations and affective contagions, thus opening the Psychology field to new modes of existence, including the discontinuous thread that constitutes the movement of this narrative